The ESCO Formula as Support for Public and Commercial Energy Projects in Poland - Joanna Kurowska-Pysz; Grzegorz Kunikowski (Energies, 2021)
The formula of engaging an energy service company (ESCO) in Poland is not a new form of accounting for investments in improving energy efficiency. The results of our survey confirm that many entities still lack sufficient knowledge about this subject. The research problem this paper is concerned with is the conditions of applying the ESCO formula (a model of investment financing with the participation of a specialised company) to support local government units and enterprises in energy-industry project development. For the purpose of this study, the research questions were formulated to analyse of the following issues: the reasons for interest in the ESCO formula and the sources of knowledge about this solution; activities and other factors that can increase or reduce interest in the ESCO formula; services in terms of ESCO formula implementation; the attractiveness of alternative instruments for financing energy industry projects, the benefits of using the ESCO formula and the influence of current and future target groups on ESCO formula development in Poland. This paper, therefore aims to recognise the conditions under which the ESCO formula can be applied by local government units and enterprises implementing energy industry projects in Poland. The research problem was solved using a triangulation of research methods: empirical qualitative research (desk research analysis, individual in-depth interviews, computer-assisted web interview (CAWI) survey, and focus group interviews) and one of the foresight methods (an expert panel). The research revealed that the lack of knowledge amongst local government units and enterprises with regard to the ESCO formula, although not unique to Poland, is insufficient to explain the low level of interest in this solution. One of the key conclusions is the need to educate local government units and enterprises on energy efficiency. This is vital to arouse their interest in the more complex ESCO implementation solutions that they have not yet investigated. Furthermore, by following and analysing the project implementation process in the ESCO formula, we can conclude that the risk generated is primarily on the part of the energy service company itself. For this reason, it is doubtful that energy service companies will invest the equity necessary to develop this challenging market. Based on the research conclusions, we indicate some recommendations that the government and related public institutions should consider in order to boost this market and support ESCO companies.